BEBERAPA SIFAT FISIS DAN KIMIA EKSTRAK TANIN - Gustan Pari (Jurnal Penelitian Hasil Hutan, 1990)
The  result  of  study on  some  physical and  chemical  properties of  tannin  ex tractiues prepared by  using  extraction method   is presented in  this  report. Treatment  conditions for  tannin  extractive   were  respectively   fineness  of  40 and  60 mesh,  extraction  temperature   were: 60°C,  80°C,  100°C  ahd raw material species  for this experiment  were Pinus merkusii, Rhizopora apiculata  and Acacia  decurrens.The result  shows that the yield of  tannin  extroctives ranges from 0,5222,75%,  tannin  content: 2,9970,76%, moisture content: 0,002225,58%, solubility in cold water:   0,0963,50%  and  tannin  content  of  residure  ranges from 0,193,75%.